Pengaruh Promosi Media Sosial Terhadap Keputusan Pembelian di Kedai Kopi Wargi Bogor - Riani Prihatini Ishak (Tourism Scientific Journal, 2022)
The development of marketing digitalization has increased significantly, this is applied to business actors, namely Kedai Kopi Wargi Bogor, which markets their products and businesses through social media. This study aims to determine the effect of social media promotion on purchasing decisions at Kedai Kopi Wargi Bogor. The research method used is a quantitative study with a population of social media consumers at Kedai Wargi Bogor using a questionnaire and assessed using a Likert scale and statistically analyzed. The results showed that promotion had a strong influence and correlation with Purchase Decisions at the Wargi Coffee Shop, Bogor. This can be seen from the R2 value obtained, indicating that promotions affect Purchase Decisions at the Wargi Coffee Shop, Bogor by 50.3% and the remaining 49.7% is influenced by other variables not assessed.